Ramadhan English Day: Using Games Method at TPQ Nurul Qomar II Paccinongan, Kabupaten Gowa - Nurfadillah; Marwah (IJOCSE: Indonesian Journal of Community Services, 2024)
Language is a communication tool that humans need when interacting with the aim of conveying ideas, ideas, thoughts and feelings. Therefore, language has an important role in everyday life, especially because English is an international language. In the current era (Artificial Intelligence era) where many children depend on AI applications which make the learning process easier but turn off their analytical power. Learning English is not just knowing the meaning, but requires a deep understanding of when a word is used and how to use it. Even though English is still a foreign language in Indonesia, it is necessary to pay attention to this from an early age for children, especially children at TPQ Nurul Qomar. Providing learning in the form of an English Day is one of the methods used to encourage children at TPQ Nurul Qomar to learn. The aim of holding English Day is to motivate children to learn English and also to provide children with an understanding of the importance of learning English. The teaching material that is the focus of the service in this activity is the alphabet which is then linked to animals using a game method. The result of the English day activities at TPQ Nurul Qomar was that the children were very enthusiastic about learning English. This can be seen when the service team encourages children to name their favorite animals in English and they compete to say their favorite animals.